(untitled) (Research, Society and Development, 2022)
Objective: Analyze the perception of health professionals about the protocols for control and prevention of hepatitis B and C: from pregnancy to breastfeeding. Method: This is a qualitative cross-sectional study, carried out in a reference maternity hospital in Pará and approved by ethics committee under the registration 2.037.289. The data collection was carried out in February 2019 and had participation of professionals and multiprofessional health residents of the maternal and childcare line. A four-item questionnaire was applied on the knowledge of procedures for the control and prevention of hepatitis B and C: from pregnancy to breastfeeding. Results: The study covered 23 participants, most of whom were multiprofessional residents (52.2%), with 34.0% suggesting that the hospital worked on health and education strategies for the community and continuing education, 3% were unaware of prenatal protocols and 13% of the delivery room to prevent vertical transmission. Regarding breastfeeding, 16% had doubts about the contraindication of seropositive mothers for hepatitis regarding the indication and support for safe breastfeeding. Conclusion: The use of prevention and control protocols for viral hepatitis still needs to be more widespread and applied, with the planning of education and health and permanent education strategies associated with the digital system as the most suitable means for reaching everyone in a contemporary world.